The Effect of Marketing Mix on Consumer Satisfaction and Loyalty for Indonesian Brand Salad Dressing “XYZ” - Christian Arianto Rahardjo; Harianto Harianto; Heny K. Suwarsinah (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2019)
XYZ’, as a salad dressing product, can help consumers to prepare meals in a short time. In Indonesia, growth in salad dressing products every year is relatively high, increasing by 120% per year. The market share of salad dressings is also getting bigger with the addition of new players and variants. The purpose of this research was identifying the attributes affecting consumers’ satisfactions and their satisfaction levels. The attributes used in this research were related to the marketing mix. Consumer loyalty is also important so that ‘XYZ’ can compete to fulfil consumer needs. This research used a quantitative descriptive method by conducting an online survey of ‘XYZ’ salad dressing consumers and direct interviews in shopping centers. The respondent criteria were females who were more than 18 years old and lived in Jabodetabek area. The technique of data processing and analysis used in this research was a quantitative descriptive analysis by using Structural Equation Modeling (SEM) and LISREL software version 8.7. Based on the results of research and evaluation on respondents, it can be concluded the marketing mix that has a significant effect on consumer satisfaction is product, price, and place. Promotion has no significant effect on consumer satisfaction. Consumer satisfaction has a significant effect on consumer loyalty. Suggestions to increase consumer satisfaction and loyalty to ‘XYZ’ brand are to sell products that meet consumer tastes and to maintain the product quality. The placement of ‘XYZ’ product in the shopping center must be taken into account to make it easy to find and maintain its product availability in the market. This can increase consumer satisfaction and lead to an increase in consumer loyalty.Keywords: consumer loyalty, consumer satisfaction, marketing mix, salad dressing, SEMAbstrak: “XYZ” sebagai salah satu produk salad dressing, dapat membantu konsumen menyiapkan makanan dalam waktu singkat. Pertumbuhan produk salad dressing setiap tahun cukup tinggi yaitu meningkat 120% tiap tahun. Pangsa pasar salad dressing juga semakin besar dengan bertambahnya pemain baru dan varian baru. Tujuan dari penelitian ini adalah untuk mengetahui atribut yang mempengaruhi kepuasan dan bagaimana tingkat kepuasan konsumennya. Atribut yang diambil dalam penelitian ini terkait dengan bauran pemasaran. Penelitian menggunakan metode deskriptif kuantitatif dengan Teknik pengolahan dan analisis data pada penelitian ini adalah analisis deskriptif kuantitatif. Alat bantu analisis menggunakan Structural Equation Modelling (SEM) dan software LISREL versi 8.7. Hasil penelitian diperoleh kesimpulan bauran pemasaran yang berpengaruh signifikan terhadap kepuasan konsumen adalah variabel produk, harga, dan tempat. Sebaliknya variabel promosi memberikan pengaruh yang tidak signifikan terhadap kepuasan konsumen. Kepuasan konsumen berpengaruh signifikan terhadap loyalitas konsumen. Saran yang dapat diberikan untuk meningkatkan kepuasan dan loyalitas konsumen produk “XYZ” adalah dengan menjaga rasa produk agar sesuai dengan selera konsumen dan menjaga kualitas produk. Penempatan produk “XYZ” di pusat perbelanjaan juga harus diperhatikan agar selalu mudah ditemukan serta menjaga ketersediaan produk di pasaran. Hal tersebut dapat meningkatkan kepuasan konsumen dan berujung pada kenaikan loyalitas konsumen.Kata kunci: bauran pemasaran, kepuasan konsumen, loyalitas konsumen, salad dressing, SEM